FENOMENA PHUBBING DALAM KOMUNIKASI ANTAR PRIBADI BAGI GENERASI MUDA - Sari, Wulan Purnama; Lady Ta, Yesha; Riwanda, Josephine Kayla; Irena, Lydia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Increasing from 2018, internet users in Indonesia have grown by 54.25% in early 2022, reaching 204.7 million users. This escalation in the number of internet users is also directly proportional to the increase in the number of social media users. There are now 191.4 million users of social media platforms, growing by 12.6% compared to the previous year. Various aspects of life are made easier by social media. However, in line with its good benefits, social media also has various negative impacts on human life, especially the younger generation. Excessive cell phone use can reduce the ability to connect, influence others, and therefore have a negative impact on interpersonal relationships. Instead of focusing on the person they are talking to, the younger generation tends to engage in phubbing or actions that insult someone in a social environment by looking at their cell phone when interacting with other people. Therefore, the solution to the problem above is exposure to the younger generation, in this case Santo Yakobus High School students, regarding overcoming phubbing in order to optimize interpersonal communication. PKM is carried out using the seminar method. This method is applied as the most effective form of socialization to overcome phubbing to optimize interpersonal communication, where discussions can be held with students, and ends with suggestions and evaluation. The mandatory output of this research is the proceedings at a scientific meeting, while the additional output is the recording of IPR. The results of the questionnaire showed that PKM activities were successful in increasing YAkobos High School students' understanding of the phubbing phenomenon and how to overcome it.